Survival and Prognostic Factors of 215 Post‐Transplant Lymphoproliferative Disorders After Solid Organ Transplantations in a Finnish Nationwide Population‐Based Study Over 30 Years - Friman, Terhi K.; Salmela, Birgitta; Helanterä, Ilkka; Åberg, Fredrik; Jahnukainen, Timo; Halme, Maija; Vaittinen, Samuli; Lommi, Jyri; Pentikäinen, Markku O.; Kovanen, Panu E.; Leppä, Sirpa; Räty, Riikka (Wiley, 2026)
Post-transplant lymphoproliferative disorder (PTLD) is a rare, dreaded complication of organ transplantation with major clinical challenges. We conducted a nationwide population-based study of all solid organ transplant (SOT) recipients (n = 6555), both adults and children, over a 30-year period in Finland. Altogether, 215 patients developed PTLD, including 146 aggressive B-cell lymphomas, in a median of 7.8 years after SOT. The incidence of PTLD was 322 per 100,000 patient-years. In median follow-up of 11.5 years after PTLD diagnoses, 155 patients deceased, 119 (55%) of them PTLD related. The median overall survival (OS) was 1.7 years for all. After curatively intended therapy (n = 165), the median OS was 6.1 years, 5-year OS rate 52%, and 5-year disease-specific survival (DSS) 58%. In all, 120 patients (56%) achieved complete remission (CR); 69% receiving first-line rituximab and 73% with chemotherapy, and their 5-year DSS rate was 79%. Relapses or second PTLD was recorded in 55 patients (36%) in a median of 1.5 years, and ten cases occurred over five years after the original PTLD diagnosis. International Prognostic Index (IPI) and age over 45 years at PTLD diagnosis were associated with inferior outcomes. Early deaths (< 100 days; n = 60; 28%) were related to progressive PTLD or treatment-related complications. However, a decreasing trend in 100-day mortality was observed, with improved DSS over the study period (1988–2002 compared with 2003–2017, p = 0.011), despite increased median age at PTLD diagnosis. In conclusion, early mortality remained high throughout the study period. In a long follow-up, the relapses were a major problem even after 5 years. PTLD related mortality rate was remarkably lower in more recent years.